Diasporic Consciousness in Desirable Daughters by Bharati Mukherjee: Examining the Journey of Self-discovery in Bharati Mukherjee's Desirable Daughters (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Bharati Mukherjee is an Indian born American novelist. Mukherjee’s novels are essential to the question of mutilation of the self, eagerness of migration, wistfulness for lost home. Desirable Daughters, explores how Tara reunites with her home family community and tradition in the way of quest of self contrast society, self-finding.